Development of Unmanned Aerial Vehicle for Agrochemical Spraying to Enhance Crop Protection - Shalzim, Kadala F.; Alfred, Ndana’acha (Kwaghe International Journal of Engineering and Information Technology, 2025)
The use of autonomous or guided unmanned aerial vehicle (UAV) is beginning to have enormous benefits in Agriculture by modernizing the ways in which farmers work not only to improve the yield and maximize profit but also the need to be healthy by avoiding direct contact with the agrochemicals used in our farmlands. The aim of this paper is to present an on-going research on the local development of agricultural spraying unmanned aerial vehicle for enhancing crop production and protection in small and medium scale maize, rice, and sugar cane plantation farmers in the Nigeria. The objective is to design and develop a practical UAV sprayer based solutions that would enable the adoption of the precision agriculture farming technique by Nigerian farmers. The proposed method involved the development of a 850 mm hexa-rotor UAV platform with an air bone spray system, the UAV uses a pixhawk flight controller, iRotor 5010/360KV motors with a1555 propellers,40A ESC and 5200mAh/ 22.2volts battery. It telemetry operates on a frequency of2.4GHz using flysky transmitter and receiver, with an ultrasonic sensor for capturing the unmanned aerial vehicle height above the ground level. In this research thrust analysis was performed tos determine the lift capacity of four propeller, the 1245, 1447, 1555 and 1655 inches in combination with 360Kv motor. And it was determined that the 1555 inches propeller out performs the other three propellers as shown in their performance plots in Spyder-Python –Anaconda. The UAV Sprayer system was implemented using the best optimal performing components, with the overall intention of developing sustainable methods in crop production and protection that would increase the crop yield that will build a resilient economy and minimize human exposure to the hazardous chemicals while optimizing both crop production and protection.